2021
DOI: 10.1101/2021.04.08.21255064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA methylation and brain dysmaturation in preterm infants

Abstract: Preterm birth is associated with dysconnectivity of structural brain networks and is a leading cause of neurocognitive impairment in childhood. Variation in DNA methylation (DNAm) is associated with early exposure to extrauterine life but there has been little research exploring its relationship with brain development. Using genome-wide DNA methylation data from saliva of 258 neonates, we investigated the impact of gestational age on the methylome and performed functional analysis to identify enriched gene s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 91 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…peak width of skeletonised metrics (Baykara et al, 2016;Blesa et al, 2020)). Nevertheless, the g-factors could carry information beyond the simple dichotomy of term vs preterm birth and could be useful for investigating other environmental or genetic/epigenetic exposures that are hypothesised to affect global white development (Boardman et al, 2014;Boardman and Counsell, 2020;Krishnan et al, 2017;Wheater et al, 2021), or for predicting neurocognitive outcomes as previously reported in adults and children (Cox et al, 2019(Cox et al, , 2016Lee et al, 2017;Penke et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…peak width of skeletonised metrics (Baykara et al, 2016;Blesa et al, 2020)). Nevertheless, the g-factors could carry information beyond the simple dichotomy of term vs preterm birth and could be useful for investigating other environmental or genetic/epigenetic exposures that are hypothesised to affect global white development (Boardman et al, 2014;Boardman and Counsell, 2020;Krishnan et al, 2017;Wheater et al, 2021), or for predicting neurocognitive outcomes as previously reported in adults and children (Cox et al, 2019(Cox et al, , 2016Lee et al, 2017;Penke et al, 2010).…”
Section: Discussionmentioning
confidence: 99%